Fishing restrictions and remoteness deliver conservation outcomes for Indonesia's coral reef fisheries. Issue 2 (4th February 2020) - Campbell, Stuart J.; Darling, Emily S.; Pardede, Shinta; Ahmadia, Gabby; Mangubhai, Sangeeta; Amkieltiela,; Estradivari,; Maire, Eva
Abstract: Coral reef fisheries depend on reef fish biomass to support ecosystem functioning and sustainable fisheries. Here, we evaluated coral reefs across 4, 000 km of the Indonesian archipelago to reveal a large gradient of biomass, from <100 kg/ha to >17, 000 kg/ha. Trophic pyramids characterized by planktivore dominance emerged at high biomass, suggesting the importance of pelagic pathways for reef productivity. Total biomass and the biomass of most trophic groups were higher within gear restricted and no‐take management, but the greatest biomass was found on unmanaged remote reefs. Within marine protected areas (MPAs), 41.6% and 43.6% of gear restricted and no‐take zones, respectively, met a global biomass target of 500 kg/ha, compared with 71.8% of remote sites. To improve conservation outcomes for Indonesia's biodiverse and economically important coral reef fisheries, our results suggest to: (1) strengthen management within Indonesia's existing MPAs and (2) precautionarily manage remote reefs with high biomass.